Preparation and characterization of Activated Carbon from Iraqi Corns Stalks (Baghdad Science Journal, 2025)
In this paper, Activated Carbon was successfully prepared from local Iraqi material namely corns stalks .Zinc chloride ZnCl2 was used as activating agent with different concentrations (20%, 40%, 60%) for 72 hours. followed by carbonization at 450 C for (2) hour. UV-Spectrophotometer used for measuring absorbance of methylene blue solutions before and after adsorption. the maximum amount adsorbed for methylene blue material of the prepared activated Carbon was studied by Langmuir adsorption isotherm. Other characteristics of the resulting activated Carbon also discussed, such as pH, Moisture Content and ash content. Finally Activated carbon prepared in this work has good properties compared to the standard samples in such a way it could be used in industrial activities due to the fact that the corn stalks available locally in our country.